Coping Students in Working on Their Thesis - Rizke Adyafnita; Khairani Khairani (Universitas Negeri Padang, 2019)
Coping is an effort to manage burdensome situations, expand effort to overcome or reduce stress. Coping that focuses on aimed at reducing or manging emotional stresses related to the situation. The purpose of this study is to describe student coping in working on scripts viewed from emotional focused coping and problem focused coping. The type of research used is descriptive research. The research population of the students of the Faculty of Education, Padang State University, who worked on their thesis in 2019 from the 2012-2015 batch of 790 students. Samples were taken using proportional random sampling technique, so that a total sample of 266 students was obtained. The study was conducted by administering the questionnaire instrumen. Data were analyzed by percentage analysis. The study shows the results (1) coping students in worling on the thesis as a whole is in the low category, (2) coping students in working on the thesis seen from emotional focused coping in in the lo category, (3) coping students in working on the thesis seen from problem focused coping is at low category.